2023
DOI: 10.1021/acs.analchem.2c04373
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of In Situ Electrochemical Regulation for Highly Enhanced Nonenzymatic Sensing of Carbaryl

Abstract: Specific and sensitive sensing of most pesticide residues relies on enzymes such as acetylcholinesterase and advanced materials, which need to be loaded on the surface of working electrodes, leading to instability, uneven surface, tedious process, and high cost. Meanwhile, employing certain potential or current in electrolyte solution could also modify the surface in situ and overcome these drawbacks. However, this method is only regarded as electrochemical activation widely applied in the pretreatment of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Therefore, 1-NA reduced the generation for DEAET–Au NCs intermediates by hole-capture competition, leading to the significantly quenching of ECL intensity of DEAET–Au NCs. Additionally, the consumption of DEAET–Au NCs excited states with 1,4-naphthoquinone (1,4-NQ) for the electro-oxidation product of 1-N was investigated . As shown in Figure E, the typical reducing agent NaBH 4 quenched the ECL intensity of DEAET–Au NCs due to its strong reducibility, consuming the electro-injected holes on the GCE surface (curve a, b).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 1-NA reduced the generation for DEAET–Au NCs intermediates by hole-capture competition, leading to the significantly quenching of ECL intensity of DEAET–Au NCs. Additionally, the consumption of DEAET–Au NCs excited states with 1,4-naphthoquinone (1,4-NQ) for the electro-oxidation product of 1-N was investigated . As shown in Figure E, the typical reducing agent NaBH 4 quenched the ECL intensity of DEAET–Au NCs due to its strong reducibility, consuming the electro-injected holes on the GCE surface (curve a, b).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Additionally, the consumption of DEAET−Au NCs excited states with 1,4-naphthoquinone (1,4-NQ) for the electrooxidation product of 1-N was investigated. 38 As shown in Figure 4E, the typical reducing agent NaBH 4 quenched the ECL intensity of DEAET−Au NCs due to its strong reducibility, consuming the electro-injected holes on the GCE surface (curve a, b). Nevertheless, in the presence of CE and 1-NA, the ECL signal of DEAET−Au NCs containing NaBH 4 was higher than that of DEAET−Au NCs without NaBH 4 (curve c, d), which was because NaBH 4 reduced 1,4-NQ in advance to avoid the occurrence of the reaction between 1,4-NQ and DEAET−Au NCs excited states.…”
Section: ■ Experimental Sectionmentioning
confidence: 90%
“…The effect of cyclic potential applied to the electrode during electrochemical activation is mainly dependent on two key factors: sweep segments and potential range. 15,17 In general, a "sweep segment" means a one-way cycle between high potential and low potential while the two segments are one circle. To explore whether changing these two parameters can further improve the signal response of MP on e-GCEs, we recorded the peak current of MP on e-GCEs under different sweep segments and potential ranges.…”
Section: Signal Response Of Mp On Various E-gcesmentioning
confidence: 99%
“…[7][8][9] However, more and more research found that the effect of electro-activation during the whole process of preparation and testing has been underestimated or even ignored. [10][11][12][13][14] Recently, electro-activated GCEs (e-GCEs), typically prepared by high-potential potentiostatic polarization or potential cycling over a wide potential range, have emerged and been applied for detecting various electro-active analytes like imidacloprid, 11,15 hydroquinone, 6 catechol, 16 carbaryl, 17 uric acid, 18 paracetamol, 19 tert-butylhydroquinone, 20 and so on. Compared with the much more widely adopted modication with biochemical elements, the advantages of e-GCEs include high stability, facile fabrication, low cost, environmental protection, and user-friendliness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation